Apoptotic effect of compound K in hepatocellular carcinoma cells via inhibition of glycolysis and Akt/mTOR/c‐Myc signaling. (15th April 2021) - Shin, Nari; Lee, Hyo‐Jung; Sim, Deok Yong; Im, Eunji; Park, Ji Eon; Park, Woon Yi; Cho, Ah Reum; Shim, Bum Sang; Kim, Sung‐Hoon
Abstract : Since the AKT/mammalian target of rapamycin (mTOR)/c‐Myc signaling plays a pivotal role in the modulation of aerobic glycolysis and tumor growth, in the present study, the role of AKT/mTOR/c‐Myc signaling in the apoptotic effect of Compound K (CK), an active ginseng saponin metabolite, was explored in HepG2 and Huh7 human hepatocellular carcinoma cells (HCCs). Here, CK exerted significant cytotoxicity, increased sub‐G1, and attenuated the expression of pro‐Poly (ADP‐ribose) polymerase (pro‐PARP) and Pro‐cysteine aspartyl‐specific protease (pro‐caspase3) in HepG2 and Huh7 cells. Consistently, CK suppressed AKT/mTOR/c‐Myc and their downstreams such as Hexokinase 2 (HK2) and pyruvate kinase isozymes M2 (PKM2) in HepG2 and Huh7 cells. Additionally, CK reduced c‐Myc stability in the presence or absence of cycloheximide in HepG2 cells. Furthermore, AKT inhibitor LY294002 blocked the expression of p‐AKT, c‐Myc, HK2, PKM2, and pro‐cas3 in HepG2 cells. Pyruvate blocked the ability of CK to inhibit p‐AKT, p‐mTOR, HK2, and pro‐Cas3 in treated HepG2 cells. Overall, these findings provide evidence that CK induces apoptosis via inhibition of glycolysis and AKT/mTOR/c‐Myc signaling in HCC cells as a potent anticancer candidate for liver cancer clinical translation.